Biosynthesised silver nanoparticles using aqueous leaf extract of Tagetes patula L. and evaluation of their antifungal activity against phytopathogenic fungi. Issue 5 (24th May 2017) - Sukhwal, Aradhana; Jain, Devendra; Joshi, Arunabh; Rawal, Pokhar; Kushwaha, Himmat S.
Abstract : In the recent decades, nanotechnology is gaining tremendous impetus due to its capability of modulating metals into their nanosize, which drastically changes the chemical, physical, biological and optical properties of metals. In this study, silver nanoparticles (AgNPs) synthesis using aqueous leaf extracts of Tagetes patula L. which act as reducing agent as well as capping agent is reported. Synthesis of AgNPs was observed at different parameters like temperature, concentration of silver nitrate, leaf extract concentration and time of reduction. The AgNPs were characterized using UV‐vis spectroscopy, scanning electron microscope with energy dispersive spectroscopy, transmission electron microscopy with selected area electron diffraction, X‐ray diffraction, Fourier transform infrared and dynamic light scattering analysis. These analyses revealed the size of nanoparticles ranging from 15 to 30 nm as well revealed their spherical shape and cubic and hexagonal lattice structure. The lower zeta potential (−14.2mV) and the FTIR spectra indicate that the synthesized AgNPs are remarkably stable for a long period due to the capped biomolecules on the surface of nanoparticles. Furthermore, these AgNPs were found to be highly toxic against phytopathogenic fungi Colletotrichum chlorophyti by both in vitro and in vivo and might be a safer alternative to chemical fungicides.